2019
DOI: 10.1007/s00415-019-09223-1
|View full text |Cite
|
Sign up to set email alerts
|

A 30 s test for quantitative assessment of a relative afferent pupillary defect (RAPD): the infrared pupillary asymmetry (IPA)

Abstract: Background: Detection of a relative afferent pupillary defect (RAPD) by the swinging-light test can be challenging in clinical practice (dark eyes, anisocoria). We developed a new method of RAPD quantification based on the recording of the Infrared Pupillary Asymmetry (IPA) with a standard optical coherence tomography (OCT) device. Methods:The diagnostic value of the IPA for detection of the RAPD was determined by Receiver Operating Characteristic (ROC) curves, Area Under the Curve (AUC).Results: Twenty-nine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The ODD consortium has therefore developed a highly sensitive ODD imaging protocol that should be employed in future studies on PHOMS in MS (see Table 1 in Malmqvist et al 5 ). Likewise, we did not quantitatively assess the relative afferent pupillary defect, which would be an interesting additional metric for visual function to be correlated to PHOMS 44,45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ODD consortium has therefore developed a highly sensitive ODD imaging protocol that should be employed in future studies on PHOMS in MS (see Table 1 in Malmqvist et al 5 ). Likewise, we did not quantitatively assess the relative afferent pupillary defect, which would be an interesting additional metric for visual function to be correlated to PHOMS 44,45 …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, we did not quantitatively assess the relative afferent pupillary defect, which would be an interesting additional metric for visual function to be correlated to PHOMS. 44,45 Clinical limitations of the study are related to the retrospective nature of the non-MS cohort. The retrospective cohort does, however, permit examining in more general terms the association of PHOMS with other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…61 There should be a central reading centre 64§Same macular area as by OCT; optic disc only if device capable to reliably image.¶Neurofilament light and heavy chains should be quantified using a sensitive and validated immunoassay; batch analyses in single laboratory strongly recommended.**Quantitative, pupillometric assessment of the RAPD 29. [68]††MRI sequences have been detailed in a consensus protocol 6.…”
Section: Novel Diagnostic Groupingsmentioning
confidence: 99%
“…A 20% intereye difference of OCT metrics has been proposed as a diagnostic for ON,6 but a series of recent validation studies showed that a 5% intereye difference gives a better sensitivity in a research setting 26–28. The intereye difference of the mGCIPL also correlates with quantification of the relative afferent pupillary deficit (RAPD) in ON 29. Taken together, OCT yields sensitive, objective and reproducible measures indicative of even small degrees of neurodegeneration.…”
Section: Novel Outcome Measuresmentioning
confidence: 99%
“…The SFM requires a trained examiner and is known to be prone to errorsubtle defects can be easily missed due to uneven illumination, or if the eye is stimulated offaxis 1 . Likewise, the interpretation of the SFM is difficult in the context of anisocoria, dark irides or poorly reacting pupils 2 . To address such issues, binocular pupillometers have been developed that can objectively quantify parameters of the pupil responses such as anisocoria, maximum and minimum pupil diameter, and dilation and constriction velocity 3 .…”
Section: Introductionmentioning
confidence: 99%